Sexual harassment from anti-discriminatory to criminal law regulation with reference to the key reasons for the invisibility of the victims - Paunović Nikola (Temida, 2019)
Ratification of the Council of Europe Convention on preventing and combating violence against women and domestic violence adopted in 2011 creates an obligation for the Party States to take the necessary legislative or other measures to ensure that sexual harassment is subject to criminal or other legal sanctions. Bearing in mind that sexual harassment, even before the adoption of this Convention, was prescribed by the anti- discriminatory and labour laws of the Party States, the paper focuses on the analysis of normative regulation of sexual harassment in the criminal legislation of the Republic of Serbia as well as in the comparative legal solutions, with the purpose of discussing the most important controversial issues concerning this new incrimination, giving particular attention to considering key reasons of objective and subjective nature that affect the invisibility of the victims of this criminal offence. Recognizing deficiencies of the criminal law regulation of sexual harassment, above all the widespread zone of punishability, de lege ferenda proposal for a normative reformulation of the essential elements of this criminal offence is provided in the concluding considerations, with the purpose of improving its application in practice.